Histopathological Effects of the Cestode parasites on fishes from the Amravati region of Vidarbha (MS) India - Gaikwad PR; Sonune MB; Nagmote SR (International Journal of Life Sciences, 2017)
The histopathological studies of infected and non-infected intestinal tissue of the host; with scolex attached to the epithelium of mucosa (villi), mature and gravid segments in lumen of intestine and among the villi. It also includes cysts of parasite in submucosa of host intestine. The transverse sections of infected intestine shows the damage to intestinal villi and submucosa. Histopathology includes the study of non-infected and infected intestine of host with reference to the cestode parasites – Circumoncobothrium shindei, 1977 Senga sonunae n.sp. Lytocestus indicus (Moge, 1925), Cotugnia aurangabadensis (Shinde, 1968), Raillietina corvina (Fuhrmann, 1909).